The level of cognitive function and recognition of emotions in older adults - Virtanen, M; Singh-Manoux, A; Batty, G; Ebmeier, K; Jokela, M; Harmer, C; Kivimäki, M (Public Library of Science, 2017)
Background: The association between cognitive decline and the ability to recognise emotions in interpersonal communication is not well understood. We aimed to investigate the association between cognitive function and the ability to recognise emotions in other people’s facial expressions across the full continuum of cognitive capacity. Methods: Cross-sectional analysis of 4069 participants (3038 men, 1031 women aged 59 to 82 years) in the Whitehall II study. Cognitive function was assessed using a 30-item Mini-Mental State Examination (MMSE), further classified into 8 groups: 30, 29, 28, 27, 26, 25, 24, and <24 (possible dementia) MMSE points. The Facial Expression Recognition Task (FERT) was used to examine recognition of anger, fear, disgust, sadness, and happiness. Results: The multivariable adjusted difference in the percentage of accurate recognition between the highest and lowest MMSE group was 14.2 (95%CI, 10.3-18.0) for anger, 15.1 (11.4-18.8) for fear, 17.8 (14.4-21.1) for disgust, 11.0 (6.6-15.4) for sadness, and 5.1 (1.9-8.3) for happiness. However, recognition of several emotions was reduced already after 1-point reduction in MMSE and with further points down in MMSE, the recognition worsened at an accelerated rate. Conclusions: The ability to recognize emotion in facial expressions is affected at an early stage of cognitive impairment and might decline at an accelerated rate with the deterioration of cognitive function. Accurate recognition of happiness seems to be less affected by a severe decline in cognitive performance than recognition of negatively valued emotions.